ANALISIS EKONOMI MESIN PENGERING PADI (ORYZA SATIVA L.) MENGGUNAKAN VERTICAL DRYER AGRINDO TIPE VRD60 DI KELOMPOK TANI HARAPAN BERSAMA DI DESA BIGO SELATAN - Paembonan, Fijar Y.; Molenaar, Robert; Rumambi, David P. (Fakultas Pertanian, Universitas Sam Ratulangi, 2020)
AbstractThis study aims to analyze the economy, total costs and economic feasibility of the rice drying process using the VRD60 type AGRINDO vertical dryer in Harapan Bersama Farmer Group in Bigo Selatan Village, Kaidipang District, Bolaang Mongondow Utara Regency, as well as the total cost of the drying process and the economic feasibility of the machine. The results showed the total drying cost of Rp. 126,908/hour. The break even point value or operational break even point of the VRD60 dryer is at an operating level of 443,620 kg/year or the equivalent of Rp140,741,126/year. Analysis of the operational feasibility of the AGRINDO vertical dryer type VRD60 dryer based on the amount of service potential available using a commercial scale calculation basis, the NPV value of Rp. 186,651,936.62, the IRR of 11%, the B/C ratio of 1.07. This condition shows that the dryer is economically feasible. Based on the conditions in the field the machines do not operate in conditions that guarantee sustainability. The sensitivity analysis shows that changes in the variable working hours per year and the price of drying services are very influential on the feasibility of operations with the lowest level being the service price of 1.43 times the total cost of drying services.Â Keywords: economics analysis. vertical dryer, paddy